Case report: Diagnostic trap: metastatic endometrial stromal sarcoma with breast metastasis - Tian, Xiaoxue; Luo, Shuai; Xu, Ting (Frontiers in Oncology, 2024)
BackgroundEndometrial stromal sarcoma (ESS) is a rare type of uterine malignancy typically classified into low-grade ESS (LG-ESS) and high-grade ESS. LG-ESS is characterized by low malignancy and limited metastasis, primarily to the lungs. Metastasis of the breast is extremely rare, posing significant challenges in clinical diagnosis and treatment.Case demonstrationA 33-year-old female with a history of two cesarean sections was diagnosed with uterine LG-ESS five months prior. She was admitted for the excision of a left breast mass discovered during a routine examination. A histopathological biopsy confirmed the mass as a breast metastasis of LG-ESS. Postoperatively, she underwent radiotherapy and chemotherapy at a cancer hospital. She has been followed up on for two years with no recurrence.ConclusionsESS with breast metastasis is extremely rare. The morphological features of ESS with breast metastasis can resemble mesenchymal and sex cord-stromal tumors, complicating imaging and pathological diagnosis, especially if there is no known history of uterine ESS. This study highlights the clinicopathological features of LG-ESS with breast metastasis, including clinical manifestations, imaging features, histopathology, immunohistochemistry, molecular genetic features, and treatment prognosis. It aims to provide new insights for the clinical diagnosis and treatment of ESS with breast metastasis.